AREAS OF INVESTMENT IN OMANI SPORT - Farouk, Ahmed (Malaysian Journal of Public Health Medicine, 2020)
Omani sport is still searching for new methods to identify its problems and achieve a vision regarding the economic problems in sport, the short-term solutions to revitalize it, and long-term solutions to maintain its stability. It hopes to rise and find an end to its funding problems in order to take off toward international winners’ podiums, especially after the good results achieved lately in several sports. Therefore, the researcher deems it necessary to identify the areas of investment in Omani sport, as potential for investment in the presence of self-finance that covers its financial needs. The researcher used the descriptive method as it is suitable to the nature of the study, and a sample of 273 subjects representing the research population. He used a questionnaire as a data collection instrument, and rank, frequency, percentage in statistical treatment. The main finding of the research was a list of the areas of investment in Omani sport in the following order: launching sports channels, TV streaming, sports professionalism, establishing sporting camps centers, academies of different games, and investment in sporting facilities. The main recommendations were to authorize Omani sporting authorities to launch TV channels to stream their matches, be based on competition with each other, and according to the rules stipulated by the Ministry of Sports Affairs and the Public Authority for Radio and Television